Human Resource Coping Strategies in „New Normal‟ and their Impact on Work Places: Systematic Review - Manjula, Dr.P.S.; K, Sindhura. (The journal of contemporary issues in business and government, 2021)
The pandemic COVID-19 challenged all the industries in their Human Resource Management systems. The impact was visible with the changing nature of work places and all organizations have to adhere to the lock down restrictions. Many of the industries except health managed their human resources for business continuity with the alternate strategy of work from home. It is interesting to observe that the changing strategy in the Human Resource (HR) practices was swift and creative. In the present study, the authors have reviewed considerable number of research articles published in various journals. The review aimed to understand the coping strategies of the Human resource practices and their impact in the phase of ‘New Normal’. The review questions of the study were a) to understand the concept of coping strategies in HR practices in ‘New normal’ after the pandemic, b) to understand the impact of ‘New Normal’ on HR, and c) to draw inferences from the available research studies. The systematic review was conducted in the following steps: Guiding review questions were framed, search for research articles published in the time period from April 2020 to November 2020, short listing of relevant articles, extraction of the data from the articles in a predesigned form, critical review of the study content by two independent authors and consensus were drawn. Twenty research articles were selected to find answers to the review questions. This paper documents the conclusion and inference drawn from the review. The review has documented the coping brilliance by reinventing new HR practices amidst unprecedented health threat, the progress of the HR from resistance to ‘New Normal’ and the lessons learnt during the new normal. The review reinforces the importance of further studies in this area of HR practices. This review study disseminates the HR practices which are documented and the findings will be useful for organizations to cope up in the post pandemic.